Exploring patterns of socio-spatial interaction in the public spaces of city through Big Data - Iranmanesh, Aminreza; Atun, Resmiye A. (Univ Politecnica Valencia, 2018)
Research on the socio-spatial aspect of cities has never been so vibrant and exciting. The form of urban life is changing and evolving with new advancements in communication and technology. Digital communication and social media have reshaped the way people as the actors of society interact with each other and with the network of the city. New social networks and widespread of mobile devices can be used to create and reinforce existing social ties. Mobile devices also change the role of citizens from consumers into producers of data; they are the new reporters, photographers, videographers of everyday life. This production creates large quantities of data known as the Big Data. Big data has created many new opportunities for researchers to investigate new aspects of cities. This paper aims to explore how people access urban public spaces through social media by taking the parameter of distance and physical proximity into account. We fried to investigate if different levels of accessibility effects the way people interact with space through social media. Through this process, the study explored different socio-spatial patterns in the city that are being affected by social media. The data was collected in two layers in the city of Lefkosa located in Northern Cyprus: first, the geo-tagged social media data was collected from the target group, and it was located on the map. Twitter as a microblogging medium was selected for data collection due to its public nature, geo-tagged abilities, and manageable short content. Second, degrees of accessibility in local and global scale was calculated using Space Syntax. The result shows the importance of local accessibility even when social media is the effective variable.
24th International Seminar on Urban Form -- SEP 27-29, 2017 -- Valencia, SPAIN
Keywords: Lefkosa; Socio-spatial Interaction; Big data; mobile devices; Twitter; Urban Network; Accessibility